Ethnic differences in risk factor profiles in subjects with coronary disease attending a state hospital in KwaZulu-Natal - Naidoo, D.P. (SA Heart Journal, 2025)
Objectives: This study compares the profile of coronary artery disease (CAD) across different ethnic groups at a tertiary referral hospital in KwaZulu-Natal. Method: We reviewed the clinical records of 1 104 subjects who underwent coronary angiography at Grey’s Hospital for suspected CAD over a 5-year period (2012 - 2016). Uni- and multivariable analysis was used to identify associations of risk factors with CAD. Results: Coronary artery disease was present in 886 subjects, of whom 69.9% were male. The majority were of Indian ethnicity (60.8%). The mean age of Africans was younger (54.9 ± 10.8 years) compared to Indians (58.0 ± 11.0 years), Coloureds (58.6 ± 12.3 years) and Whites (60.0 ± 10.5 years) (p=0.001). The prevalence of premature CAD (PCAD) (<55 years in males and <65 years in females) was 46% of males and 66,7% in females. Most African females (84,6%, p=0.01) and white females (75,6%, p=0.01) presented with PCAD. ST-elevation myocardial infarction was the most frequent presentation among African subjects (n=99, 66.0%), followed by Whites (n=76, 45.2%) and Indians (n=240, 44.5%), and least common among Coloureds (n=11, 37.9%) (p<0.001). The most prevalent risk factors were dyslipidaemia (95.1%), hypertension (70.3%), smoking (67.4%) and diabetes (57.2%). The prevalence of smoking was lowest in the African group (51.3%) compared to about 66% in the other groups (p<0.001) (Table I). About 80% of Indians and Whites had clustering of 3 or more risk factors compared to 39.3% of Africans (p<0.001). A family history of CAD lowest among African (n=13, 8.7%) and Coloured subjects (n=11,37.9%) (p<0.001) and a history of previous MI was obtained in 5.3% of African subjects compared to >23% in each of the other ethnic groups (p<0.001). Single vessel disease was commoner among Africans (48.7%), while Indians had more triple vessel disease (47.7%), (p<0.001). Univariate analysis identified risk factors and ethnicity (Indians, p=0.02) and Whites, p=0.02) as being associated with CAD, but on multivariable analysis ethnicity fell away. Age (46 - 65 years: OR: 2.2 [1.5 - 3.3], age >65 years: OR: 4.8 [2.8 - 8.2], male gender (OR: 2.7 [1.9 - 3.9]), history of smoking (OR: 2.0 [1.4 - 3.1] (all p<0.001) as well as diabetes (OR: 1.7 [1.2 - 2.4], p=0.005) and atherogenic dyslipidaemia (OR: 1.7 [1.2 - 2.4], p=0.004) were independent cardiovascular risk factors associated with the presence of CAD. Conclusion: Major risk factors were associated with CAD at a young age across all race groups. Although Africans had a lower risk factor burden, the low prevalence of a family history of MI and near absence of a previous history of MI indicate that recent environmental and / or lifestyle changes that have contributed to the emergence of CAD, often premature, in this group.